Is SMEs Able to Construct Business Strategy to Improve Its Performance Using Its Own Ability? (Study On SMEs Karawo Handicraft in City of Gorontalo, Indonesia) - Ariawan Ariawan; Made Sudarma; Djumahir Djumahir; Ghozali Maski (Journal of International Conference Proceedings (JICP), 2018)
The objectives of this study were to analyze and investigate the human capital resource of SMEs to achieve the expected level of performance and to see if the quality of human capital had been appropriate enough to be able to apply certain business strategy. This study also intended to see if the cost leadership strategy, differentiation strategy, as well as appropriate focus strategy to improve the performance of SMEs. This study employed a survey design in which researcher conducted a survey to managers or owner of 68 SMEs of Karawo handicraft in Gorontalo city. This study also employed the structural equation or PLS approach using warpPLS application to analyze the data. The finding of this study showed that the ability of the human capital owned by the SMEs had not yet maximized in improving its performance. The role of the mediation business strategy (cost leadership strategy and differentiation strategy) have been appropriate and matched the ability of the human capital to improve the performance of SMEs. The result of this study enriches the body of knowledge related to the resource based theory and the development of strategic management of the human capital investment for the implementation of business strategy to achieve good performance and system. This study also offers practical benefit for managers or owners of SMEs, and government in developing the business. The data were collected using cross sectional strategy by analyzing the opinions and perception of the managers or owners of the business. Future researchers are encouraged to expand this by involving bigger number of sample and broader scope of study. Future researcher may also develop this study using mix method research design to verify and take action on the interesting result of this study related to the implementation of focus strategy based on the ability of the human capital which has been confirmed to have the highest coefficient path, yet did not have significant effect to the improvement of the performance without the involvement of mediational variables such as the combination of focus-cost strategy or focus-differentiation strategy. Keyword : Human capital, business strategy, cost leadership strategy, differentiation strategy, focus strategy, performance, SMEs